Legal Aspects of Student Loans in the Context of Increased Financial Inclusion - Nurhilmiyah, Nurhilmiyah (Indonesian Journal Education, 2024)
Increasing financial inclusion is one of the main agendas in sustainable economic development. One of the instruments that plays an important role in this is student loans, which provide access to funding for students to continue their higher education. This paper analyzes the legal aspects that govern student loans in Indonesia, including government policies, banking regulations, and consumer protection in financial transactions. In addition, the challenges faced in the implementation of student loans were also discussed, such as the risk of default, transparency of terms and conditions, and dispute resolution mechanisms. Using normative legal research methods, and using a legal and regulatory approach, this study aims to identify existing regulatory weaknesses and provide policy recommendations to increase the effectiveness of student loans as an instrument of financial inclusion. The results of this study are expected to contribute to the formulation of a more inclusive and equitable financial policy for students in Indonesia.